The Challenges of Principals in Building Student’s Character - Ahmad Lani; Ari Safar Wadi (LPPM STIKes SITI HAJAR dan Insight Power, 2023)
This study aims to identify the challenges faced by school principals in building student character and its solutions. This study applied a qualitative research method. The informants in this study were selected using a purposive sampling method based on research needs. There were 11 informants consisting of 2 school principals and 9 teachers. Interview was a data collection technique used in this study. To analyze the data, the researcher administrated the Atlas.ti software which tended to thematic analysis models. The results of the study illustrate that the school principal faced two types of challenges in shaping student character, namely in the form of internal and external issues. Internally, school principal encountered problem related to the school management related in term of the limited educational staff such as teachers and staff, insufficient budget and finances, and learning distances. Meanwhile, the external issue is associated with the violations of school rules and regulations that have to do with students and the parent. In this case, students did not actively engage in the school activities, both inside and outside the classroom. On the other hand, the parent was less concerned about their children's future education. To solve these problems, there is an effective solution. Regarding internal issues, the school principal recommended to strengthen school management with a number of ways, including scheduling teachers in teaching, optimizing budgeting and financing, and facilitating students who need an assistance. Meanwhile, to resolve external issues, the school principal suggest to take some actions against both students and parents. In dealing with the students, the school principal requires to conduct counseling guidance, student teaching student (STS), and smart parenting. Meanwhile, to the parents, the school principal proposes to organize an inspiring talk and smart parenting.Keyword: School Principal, Parent, Student, Character Building, Challenge, Solution